Value of ultrasound in the diagnosis of acute appendicitis. Experience with 30 cases - Acevedo, Carlos; Harguindeguy, Martín; Caraballo, Mónica; Escudero, Bolívar; Santi, Cono; Voelker, Ricardo (Cirugía del Uruguay, 1996)
With the aim of evaluating the diagnostic precision of ultrasonography with graduated compression of the right iliac fossa in the diagnosis of acute appendicitis, this method was evaluated in 3,0 patients with clinical suspicion of this pathology